2015
DOI: 10.1111/cas.12692
|View full text |Cite
|
Sign up to set email alerts
|

MT95‐4, a fully humanized antibody raised against aminopeptidase N, reduces tumor progression in a mouse model

Abstract: Aminopeptidase N (APN/CD13) is involved in tumor cell invasion and tumor angiogenesis and is considered a promising therapeutic target in the treatment of cancer. To develop a novel monoclonal antibody-based cancer therapy targeting APN/CD13, we established a fully humanized anti-APN/CD13 monoclonal antibody, MT95-4. In vitro, MT95-4 inhibited APN/CD13 enzymatic activity on the tumor cell surface and blocked tumor cell invasion. B16 mouse melanoma cells stably expressing human APN/CD13 were also established an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 23 publications
1
8
0
Order By: Relevance
“…Our results verify the critical role of APN dynamics in CoV infection and catalysis, and demonstrate that the open APN structure is inactive in peptide hydrolysis. Anti-APN antibodies that inhibit APN activity and reduce tumor growth 25,33 likely block ectodomain movements. The allosteric inhibition of APN functions shown here using viral proteins and drugs is likely to be due to suppression of APN transient conformational states, as shown for other enzymes 34 .…”
Section: Discussionmentioning
confidence: 99%
“…Our results verify the critical role of APN dynamics in CoV infection and catalysis, and demonstrate that the open APN structure is inactive in peptide hydrolysis. Anti-APN antibodies that inhibit APN activity and reduce tumor growth 25,33 likely block ectodomain movements. The allosteric inhibition of APN functions shown here using viral proteins and drugs is likely to be due to suppression of APN transient conformational states, as shown for other enzymes 34 .…”
Section: Discussionmentioning
confidence: 99%
“…To examine the efficacy of APN/CD13 as a therapeutic target in MPM, we tested the antitumour effect of MT95-4, a fully humanised anti-APN/CD13 mAb established in our laboratory [25], in an orthotopic implantation mouse model of MPM, using MPM cells exhibiting high or low APN/CD13 expression. We found that MT95-4 administration suppressed tumour progression and angiogenesis only in tumours exhibiting high APN/CD13 expression.…”
Section: Discussionmentioning
confidence: 99%
“…MT-95-4 was developed in our laboratory as previously reported [25] and cisplatin was purchased from Nippon Kayaku (Tokyo, Japan). Male severe combined immunodeficient (SCID) mice (6 weeks old) were purchased from CLEA Japan (Osaka, Japan).…”
Section: Reagents and Animalsmentioning
confidence: 99%
See 1 more Smart Citation
“…H1299 and A549 cells have been shown to express high and low levels of APN, respectively . Similarly, we found that APN was overexpressed in H1299, but not in A549 cells (Figure S6).…”
Section: Figurementioning
confidence: 99%